Pengaruh Edukasi Postpartum terhadap Kemampuan Perawatan Bayi dan Pemberian ASI Eksklusif Pada Ibu Primipara Post Sectio Caesarea di Rumah Sakit Efarina Pematangsiantar - Santi Widya; Siti Nurul; Sihombing, Renta (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
The postpartum period is a critical time for mothers to adapt to their new role, especially for primiparous mothers who undergo cesarean section (CS). Postoperative conditions often cause limited mobility and pain that can affect the mother's ability to care for her baby and provide exclusive breastfeeding. One effective intervention that can help mothers face this transition is comprehensive postpartum education. This study aims to determine the effect of postpartum education on the ability to care for babies and provide exclusive breastfeeding in primiparous mothers after cesarean section at Efarina Etaham Hospital, Pematang Siantar. The research design used was a quasi-experimental approach with a pre-test and post-test control group design. The study sample consisted of primiparous mothers after cesarean section who met the inclusion criteria, selected using a purposive sampling method. The research instruments were an observation sheet on baby care skills and a questionnaire on exclusive breastfeeding. Data analysis was performed using paired t-test and independent t-test to determine differences in abilities before and after education. The results showed a significant increase in infant care skills and exclusive breastfeeding practices after postpartum education (p < 0.05). Therefore, it can be concluded that postpartum education has a positive effect on improving the ability of primiparous mothers after cesarean section to care for their babies and provide exclusive breastfeeding.